2014
DOI: 10.1111/ijlh.12199
|View full text |Cite
|
Sign up to set email alerts
|

Migraine and erythrocyte biology: a review

Abstract: Summary Migraine is a common disabling headache disorder that is conventionally classified according to the presence or absence of aura. The pathogenesis of this disorder entails a complex interplay of neurovascular factors, that trigger reduction of cerebral blood flow followed by reactive vasodilatation. Despite major emphasis has been placed on the investigation of putative biomarkers that could predict response to specific treatments and prophylaxis, less focus has been directed at the association between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…As we know, cerebral vascular dysfunction is always induced by abnormal levels of vasoactive substances, such as ET-1, NO and NOS. Recent studies have highlighted a potentially important role for the biological endothelial function in the migraine pathophysiology [26]. It involved the most potent endothelial-derived constricting factor, ET-1, and its endothelial counterpart, NO, in the vascular changes during migraine attacks [27].…”
Section: Discussionmentioning
confidence: 99%
“…As we know, cerebral vascular dysfunction is always induced by abnormal levels of vasoactive substances, such as ET-1, NO and NOS. Recent studies have highlighted a potentially important role for the biological endothelial function in the migraine pathophysiology [26]. It involved the most potent endothelial-derived constricting factor, ET-1, and its endothelial counterpart, NO, in the vascular changes during migraine attacks [27].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous researchers have suggested that hematological changes are closely associated with various diseases, including myelodysplastic syndrome, laryngeal squamous cell cancer, stable coronary artery disease, stroke, and acute pulmonary embolism (Nayak et al, 2011 ; List et al, 2012 ; Zorlu et al, 2012 ; Ayhan et al, 2013 ; Sahin et al, 2015 ; Soderholm et al, 2015 ; Hsueh et al, 2017 ). Moreover, recent studies have indicated that migraine conditions may be related to some hematological parameters, especially high hemoglobin levels and broad red blood cell distribution width (Celikbilek et al, 2013 ; Lippi et al, 2014 ). Thus, hematological changes are an attractive area for improving our understanding of HAH, although we are not aware of any studies that have examined this issue.…”
Section: Introductionmentioning
confidence: 99%
“…There is also evidence that erythrocyte is a modulator in the metabolism of NO, a potent vasodilator agent. [ 12 ] The increased frequency of migraine in essential thrombocythemia supports the fact that the increased platelets can also lead to headache. Migraine is the most common vaso-occlusive symptom in essential thrombocythemia.…”
Section: Discussionmentioning
confidence: 95%
“…However, several studies have underlined the relationship between increased hemoglobin and headache. [ 12 ] In a population study conducted on female patients, the likelihood of migraine was reported to decrease in patients with a hemoglobin level of <11.5g/dL. [ 13 ] Headaches associated with chronic altitude sickness and polycythemia have also been associated with higher hemoglobin levels.…”
Section: Discussionmentioning
confidence: 99%